Immunomodulation by Trypanosoma cruzi: Toward Understanding the Association of Dendritic Cells with Infecting TcI and TcII Populations - da Costa, Thiago Alvares (Hindawi Publishing Corporation, 2014)
Dendritic cells (DCs) are major immune components, and depending on how these cells are modulated, the protective host immune response changes drastically. Trypanosoma cruzi is a parasite with high genetic variability and modulates DCs by interfering with their capacity for antigen recognition, migration, and maturation. Despite recent efforts, the association between DCs and T. cruzi I (TcI) and TcII populations is unknown. Herein, it was demonstrated that AQ1.7 and MUTUM TcI strains present low rates of invasion of bone marrow-derived DCs, whereas the 1849 and 2369 TcII strains present higher rates. Whereas the four strains similarly induced the expression of PD-L1, the production and expression of IL-10 and TLR-2, respectively, in DCs were differentially increased. The production of TNF-α, IL-12, IL-6, and CCL2 and the expression of CD40, CD80, MHC-II, CCR5, and CCR7 changed depending on the strain. The 2369 strain yielded the most remarkable results because greater invasion correlated with an increase in the levels of anti-inflammatory molecules IL-10 and PD-L1 but not with a change in the levels of TNF-α, MHC-II, or CD40 molecules. These results suggest that T. cruzi strains belonging to different populations have evolved specific evasion strategies that subvert DCs and consequently the host response.